2016
DOI: 10.1016/j.tranon.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Data on Efficacy of 10 Drug-Radiation Combinations: Evaluations, Concerns, and Recommendations

Abstract: BACKGROUND: Clinical testing of new therapeutic interventions requires comprehensive, high-quality preclinical data. Concerns regarding quality of preclinical data have been raised in recent reports. This report examines the data on the interaction of 10 drugs with radiation and provides recommendations for improving the quality, reproducibility, and utility of future studies. The drugs were AZD6244, bortezomib, 17-DMAG, erlotinib, gefitinib, lapatinib, oxaliplatin/Lipoxal, sunitinib (Pfizer, Corporate headqua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 72 publications
0
41
0
Order By: Relevance
“…While regrowth delay assays may not necessarily correspond to local tumor control, they are useful for evaluating drug-radiation interaction, mechanisms of action and microenvironmental effects. The initial models may be xenografts as are now employed or newer models from patient-derived tumors with the models selected based on their utility for predicting clinical results (16). …”
Section: Toward Improved Pre-clinical Models Of Radiation Modifiersmentioning
confidence: 99%
See 1 more Smart Citation
“…While regrowth delay assays may not necessarily correspond to local tumor control, they are useful for evaluating drug-radiation interaction, mechanisms of action and microenvironmental effects. The initial models may be xenografts as are now employed or newer models from patient-derived tumors with the models selected based on their utility for predicting clinical results (16). …”
Section: Toward Improved Pre-clinical Models Of Radiation Modifiersmentioning
confidence: 99%
“…This result may be due in part to the quality and validity of the pre-clinical data. Stone et al (16) after examining the details of 125 reported in vitro and in vivo preclinical studies on radiation-modifiers concluded that future preclinical studies must include: a) use of appropriate preclinical models that best represent the clinical setting of extant “standard-of-care” multi-modality cancer therapy, b) fastidious calibration and dosimetry of radiation sources (17), c) detailed and accurate descriptions of experimental methodology and results, and d) clinically relevant drugs, doses, schedules, and assay conditions. Of critical importance is the recognition that the mechanism of action of a molecular-targeted drug may be different when used by itself to target a specific tumor pathway compared to how it affects combination therapy that includes radiation.…”
Section: Introductionmentioning
confidence: 99%
“…This also raises critical questions for translational brain tumor research in general: What is the optimal tumor burden at the start of preclinical survival or tumor growth-delay studies, and what is the best modality for determining enrollment threshold (BLI, MRI, histopathology, etc.) (discussed below) [75,80,81]? Additionally, evidence of the importance of the tumor microenvironment in governing the response to radiation continues to emerge [82]), highlighting an obvious shortcoming of PDOX models.…”
Section: Outstanding Questions and Future Directionsmentioning
confidence: 99%
“…If they perform calibration, most facilities use a variation of the approach described in TG-61, a document describing methods to calculate an absorbed dose to water for 40-300 kVp x-rays [47][48][49]. Far too many publications fail to provide sufficient detail to enable replication of radiation delivery and even fewer provide details regarding the frequency and type of calibration performed [50]. At our institution, monthly quality assurance is performed by a member of the UW Calibration Lab using a custom-built compact 4x4cm phantom and Gafchromic EBT3 film which has known spatial precision and relatively flat energy response [51].…”
Section: Radiation Deliverymentioning
confidence: 99%
“…The ease of studying drug or radiation sensitivity in vitro has allowed for the discovery of chemotherapeutics and molecularly targeted agents that sensitize cells to RT [54,55]. These studies are then translated into murine models with varying rates of success and unfortunately, these studies are rarely translated to clinic with a disappointing number of clinical advances [50,[55][56][57]. Hypotheses explaining this divide include: 1) disparity in tumor microenvironment (TME) between animal models and human tumors; 2) PK/PD challenges limiting drug availability; 3) failure to confirm target inhibition; 4) unanticipated overlapping toxicities; 5) imprecise and inaccurate RT dose delivery impairing interpretation of data; and 6) testing in a limited number of cell lines; and, 7) failure to test with RT.…”
Section: Challenges In Drug and Radiation Deliverymentioning
confidence: 99%